Impact of CYP2D6, CYP3A5, and ABCB1 Polymorphisms on Plasma Concentrations of Donepezil and Its Metabolite in Patients With Alzheimer Disease. Issue 3 (June 2021) - Kagawa, Yoshiyuki; Yamamoto, Yoshiaki; Ueno, Ayami; Maeda, Toshio; Obi, Tomokazu
Abstract : Background: Donepezil is one of the most commonly prescribed drugs for the treatment of Alzheimer disease. It is predominantly metabolized through CYP2D6 and to a lesser extent by CYP3A4/5. There are conflicting reports regarding the influence of CYP2D6, CYP3A5, and ABCB1 polymorphisms on the plasma concentration of donepezil. This study investigated the influence of these polymorphisms and sex on the plasma concentrations of donepezil and its active metabolite, 6-O-desmethyl donepezil (6ODD), in 47 patients with Alzheimer disease. Methods: Plasma donepezil and 6ODD concentrations were measured using liquid chromatography tandem mass spectrometry. Sex, the concomitant use of psychotropics, and CYP2D6, CYP3A5, and ABCB1 polymorphisms were analyzed as possible influencers. Results: The mean plasma concentrations of donepezil and 6ODD were well correlated (R 2 = 0.418). The mean plasma concentration ratio of donepezil to 6ODD (metabolic ratio) was significantly lower in intermediate metabolizers of CYP2D6 than in extensive metabolizers. The metabolic ratio in patients receiving psychotropics was significantly lower than in those not receiving psychotropics. Among intermediate metabolizers, patients positive for CYP3A5 *3/*3 showed a significant increase in plasma mean 6ODD concentrations when compared with those who did not express this gene (CYP3A5 *1/*1 or *1/*3). Conclusions: Results indicate that the mean plasma concentration ratio of donepezil to 6ODD is associated with CYP2D6 polymorphism and the concomitant use of psychotropics in patients with Alzheimer disease. In intermediate metabolizers, CYP3A5 may play a significant role in the metabolism of donepezil. Abstract : Supplemental Digital Content is Available in the Text.